Identification Of Teacher Difficulties In The Process Of Learning Mathematics For Class III Students At SDN 09 Taliwang West Sumbawa - Yanti, Fithri Kurnia Zenra; Dewi, Nurul Kemala; Rosyidah, Awal Nur Kholifatur (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to explain and identify teacher difficulties in the mathematics learning process for third grade students at SDN 09 Taliwang West Sumbawa, the factors causing teacher difficulties in the mathematics learning process for third grade students at SDN 09 Taliwang West Sumbawa and the efforts that can be made by third grade teachers at SDN 09 Taliwang Sumbawa. West to overcome difficulties in the third grade mathematics learning process at SDN 09 Taliwang, West Sumbawa. This type of research is a special study research with a qualitative approach. Data collection methods used are interviews and observation. The data analysis technique used is data reduction, presentation, and conclusion drawing. The technique of determining the validity and validity of the data uses the source. The results of this study indicate that the difficulties experienced by class III teachers at SDN 09 Taliwang West Sumbawa in the mathematics learning process are in terms of planning, implementation, and evaluation. Teachers experience difficulties in the form of: (1) difficulty in determining the type of assessment; (2) difficulty in conveying the material; and (3) difficulties in evaluating students.